Threat management priorities for conserving Antarctic biodiversity - Lee, Jasmine R.; Terauds, Aleks; Carwardine, Josie; Shaw, Justine D.; Fuller, Richard A.; Possingham, Hugh P.; Chown, Steven L.; Convey, Peter; Gilbert, Neil; Hughes, Kevin A.; McIvor, Ewan; Robinson, Sharon A.; et al. (PLOS Biology, 2022)
Antarctic terrestrial biodiversity faces multiple threats, from invasive species to climate change. Yet no large-scale assessments of threat management strategies exist. Applying a structured participatory approach, we demonstrate that existing conservation efforts are insufficient in a changing world, estimating that 65% (at best 37%, at worst 97%) of native terrestrial taxa and land-associated seabirds are likely to decline by 2100 under current trajectories. Emperor penguins are identified as the most vulnerable taxon, followed by other seabirds and dry soil nematodes. We find that implementing 10 key threat management strategies in parallel, at an estimated present-day equivalent annual cost of US$23 million, could benefit up to 84% of Antarctic taxa. Climate change is identified as the most pervasive threat to Antarctic biodiversity and influencing global policy to effectively limit climate change is the most beneficial conservation strategy. However, minimising impacts of human activities and improved planning and management of new infrastructure projects are cost-effective and will help to minimise regional threats. Simultaneous global and regional efforts are critical to secure Antarctic biodiversity for future generations.
Publisher: Public Library of Science
Keywords: Antarktis; biodiversitet; forvaltning; pingviner

Genomic insights into the secondary aquatic transition of penguins - Cole, Theresa L.; Zhou, Chengran; Fang, Miaoquan; Pan, Hailin; Ksepka, Daniel T.; Fiddaman, Steven R.; Emerling, Christopher A.; Thomas, Daniel B.; Bi, Xupeng; Fang, Qi; Ellegaard, Martin R.; Feng, Shaohong; et al. (Nature Communications, 2022)
Penguins lost the ability to fly more than 60 million years ago, subsequently evolving a hyper-specialized marine body plan. Within the framework of a genome-scale, fossil-inclusive phylogeny, we identify key geological events that shaped penguin diversification and genomic signatures consistent with widespread refugia/recolonization during major climate oscillations. We further identify a suite of genes potentially underpinning adaptations related to thermoregulation, oxygenation, diving, vision, diet, immunity and body size, which might have facilitated their remarkable secondary transition to an aquatic ecology. Our analyses indicate that penguins and their sister group (Procellariiformes) have the lowest evolutionary rates yet detected in birds. Together, these findings help improve our understanding of how penguins have transitioned to the marine environment, successfully colonizing some of the most extreme environments on Earth.
Keywords: Sørishavet; evolusjon; fylogenetikk; ornitologi; pingviner

The foraging behavior of nonbreeding Adélie penguins in the western Antarctic Peninsula during the breeding season - Oosthuizen, W. Chris; Pistorius, Pierre A.; Korczak-Abshire, Malgorzata; Hinke, Jefferson T.; Santos, Mercedes; Lowther, Andrew D. (Ecosphere, 2022)
Abstract Information on marine predator at-sea distributions is key to understanding ecosystem and community dynamics and an important component of spatial management frameworks that aim to identify regions important for conservation. Tracking data from seabirds are widely used to define priority areas for conservation, but such data are often restricted to the breeding population. This also applies to penguins in Antarctica, where identification of important habitat for nonbreeders has received limited attention. Nonbreeding penguins are expected to have larger foraging distributions than breeding conspecifics, which may alter their interactions with physical environmental factors, conspecifics, other marine predators, and threats. We studied the movement behavior of nonbreeding Adélie penguins tracked during the 2016/2017 breeding season at King George Island in the South Shetland Islands, Antarctica. We quantify how nonbreeding penguins' horizontal moment behavior varies in relation to environmental conditions and assess the extent of spatial overlap in the foraging ranges of nonbreeders and breeders, which were tracked over several years. Nonbreeders increased their prey search and area-restricted foraging behavior as sea surface temperature and bottom depths decreased, and in response to increasing sea ice concentration. Nonbreeders tended to transit (high directional movement) over the relatively deep Central Basin of the Bransfield Strait. The majority of foraging behavior occurred within the colder, Weddell Sea?sourced water of the Antarctic Coastal Current (incubation) and in the Weddell Sea (crèche). The utilization distributions of breeders and nonbreeders overlapped in the central Bransfield Strait. Spatial segregation was greater during the crèche stage of breeding compared to incubation and brood, because chick provisioning still constrained the foraging range of breeders to a scale of a few tens of kilometers, while nonbreeders commenced with premolt foraging trips into the Weddell Sea. Our results show that breeding and nonbreeding penguins may not be impacted similarly by local environmental variability, given that their spatial and temporal scales of foraging differ during some part of the austral summer. Our study highlights the need to account for different life history stages when characterizing foraging behavior of marine predator populations. This is particularly important for ?sentinel? species monitored as part of marine conservation and ecosystem-based management programs.
Publisher: John Wiley & Sons, Ltd
Keywords: Antarktis; ornitologi; pingviner; sjøfugler; økologi

Foraging behaviour of sympatrically breeding macaroni (Eudyptes chrysolophus) and chinstrap (Pygoscelis antarcticus) penguins at Bouvetøya, Southern Ocean - Narvestad, Audun; Kovacs, Kit M.; Lydersen, Christian; Lowther, Andrew D. (Polar Research, 2022)
Species with similar ecological requirements that overlap in range tend to segregate their niches to minimize competition for resources. However, the niche segregation possibilities for centrally foraging predators that breed on isolated Subantarctic islands may be reduced by spatial constraints and limitations in the availability of alternative prey. In this study we examined spatial and trophic aspects of the foraging niches of two sympatrically breeding penguin species, macaroni (Eudyptes chrysolophus; MAC) and chinstrap (Pygoscelis antarcticus; CHIN) penguins, at Bouvetøya over two breeding seasons. To measure at-sea movements and diving behaviour, 90 MACs and 49 CHINs were equipped with GPS loggers and dive recorders during two austral summer breeding seasons (2014/15 and 2017/18). In addition, blood samples from tracked birds were analysed for stable isotopes to obtain dietary information. CHINs displayed marked interannual variation in foraging behaviour, diving deeper, utilizing a larger foraging area and displaying enriched values of δ15N in 2014/15 compared to the 2017/18 breeding season. In contrast, MACs dove to similar depths and showed similar δ15N values, while consistently utilizing larger foraging areas compared to CHINs. We suggest that low krill abundances in the waters around Bouvetøya during the 2014/15 season resulted in CHINs shifting toward a diet that increased their niche overlap with MACs. Our findings may partly explain the decreasing number of breeding CHINs at the world’s most remote island, Bouvetøya, while also highlighting the importance of characterizing niche overlap of species using multi-season data sets.
Keywords: Bouvetøya; NARE ekspedisjoner; biotelemetri; marin biologi; pingviner